KORELASI PANJANG LENGAN BAWAH DAN TINGGI BADAN MAHASISWI SUKU BANJAR FAKULTAS KEDOKTERAN UNIVERSITAS LAMBUNG MANGKURAT - Iwan Aflanie; Nurul Qomariah; Mashuri Mashuri (Berkala Kedokteran, 2017)
Abstract: Estimated height has an important role in identifying unknown bodies, incomplete, and the residual bone. Measurements in the long bones such as the forearm are better used to determine the height because it is the best result among the other members of the body size. The purpose of this study was to analyzed a correlation between the forearm length with the height of Banjar Tribe’s students of Medical Faculty of Lambung Mangkurat University and to obtain height estimation formula based on the forearm length in Banjar Tribe’ female. The research method is an analytical observation with cross sectional approach. The research subjects were taken by purposive sampling with samples of 52 people and were analyzed by Pearson correlation and linear regression analysis. The results of Pearson test showed that the value of p = 0,00 for the right and left arm with the value of r = 0.974 for the right arm and r = 0.972 for the left arm, which means there is a very strong relationship between the forearm length with height. It is concluded that there is a very strong correlation between the forearm length with students height of Banjar tribe Medical Faculty of Lambung Mangkurat University with height estimation formula Height = 63,838 + 3,693 x length of the right forearm and Height = 61,873 + 3,780 x left forearm length.